Understanding the Other Europe: Philip Roth’s Writings on Prague. - Bryla, Martyna Marika (Editorial de la Universidad de Sevilla, 2013)
The aim of this essay is to explore the representation and significance of post-war Prague in the works of one of the finest contemporary American authors, Philip Roth. Kafka’s hometown is the locale of The Prague Orgy (1985) and one of David Kepesh’s stops on his summer tour of Europe in The Professor of Desire (1977). It also features prominently in the interviews and conversations conducted with and by Roth at the time when the Iron Curtain still separated Eastern Europe from the rest of the world. This essay analyzes Roth’s take on the complex Czechoslovak reality and discusses how the writer’s travels to Prague and his friendship with dissident authors shaped his views on the nature of literature and the position of the writer in society. The author also argues that through his writing Roth challenges certain Western stereotypes about cultural life under communism
Keywords: Escritores disidentes - Europa oriental; Comunismo; Kafka, Franz (1883-1924); Philip Roth; Eastern Europe; Prague; Franz Kafka; Dissident writers; Communism